2009
DOI: 10.1016/j.jvs.2008.08.012
|View full text |Cite
|
Sign up to set email alerts
|

A population-based case-control study of the familial risk of abdominal aortic aneurysm

Abstract: In this nationwide survey, the relative risk of developing AAA for first-degree relatives to persons diagnosed with AAA was approximately doubled compared to persons with no family history. Neither the gender of the index person nor the first-degree relative influenced the risk of AAA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
92
1
8

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(101 citation statements)
references
References 17 publications
0
92
1
8
Order By: Relevance
“…20 A populationbased study in Sweden using national registries found that the relative risk of AAA for the firstdegree relatives of both male and female AAA patients was similar. 22 …”
Section: Human Aaa Studies Risk Factors For Aaa In Men and Womenmentioning
confidence: 99%
“…20 A populationbased study in Sweden using national registries found that the relative risk of AAA for the firstdegree relatives of both male and female AAA patients was similar. 22 …”
Section: Human Aaa Studies Risk Factors For Aaa In Men and Womenmentioning
confidence: 99%
“…5,6,[9][10][11] A review of observational studies on the risk of AAA among smokers 53 indicated that smokers have a higher risk of AAA than never smokers; current smokers have a higher risk of developing AAA than former smokers; and those who smoke more than 20 cigarettes a day have a higher risk of AAA than those who smoke less. In relation to growth and rupture of an AAA, a meta-analysis conducted by the RESCAN collaboration 54 found that current smoking has a modest impact on growth of an AAA and doubles the risk of rupture.…”
Section: Considerations For Implementationmentioning
confidence: 99%
“…7,8 Other risk factors for the development of an AAA include advanced age 9 and family history of AAA. 10,11 Coronary artery disease, atherosclerosis, hypercholesterolemia and hypertension have weaker associations with AAA. 8,12 Patients with diabetes appear less likely to develop AAA.…”
mentioning
confidence: 99%
“…Data from a Swedish population study demonstrated that a family history of AAA increased the risk of AAA about 2 fold, (Larsson et al, 2009). Although the benefits of screening for AAA in the presence of a family history of aneurysm has not been formally assessed, (Moll et al, 2011).…”
Section: Family Historymentioning
confidence: 99%